2011
DOI: 10.1111/j.1530-0277.2011.01521.x
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Response to Alcohol Challenge: A Quantitative Review

Abstract: Background Individual differences in subjective response to alcohol, as measured by laboratory-based alcohol challenge, have been identified as a candidate phenotypic risk factor for the development of alcohol use disorders (AUDs). Two models have been developed to explain the role of subjective response to alcohol, but predictions from the two models are contradictory, and theoretical consensus is lacking. Methods This investigation used a meta-analytic approach to review the accumulated evidence from alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
222
3
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(244 citation statements)
references
References 78 publications
16
222
3
3
Order By: Relevance
“…These findings are generally consistent with the LLRFbut not the differentiatorF model of vulnerability for AUDs (Quinn and Fromme, 2011;Morean and Corbin, 2010), suggesting that individuals with the BPP experienced a generalized decreased awareness of intoxication, which was not biphasic in character. Although the origins of this decreased awareness remain unclear, one possibility is that previous experiences of non-substancerelated mood elevation mean that individuals with BPP are less likely to attribute ethanol-induced mood variation (ie, intoxication) to alcohol.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These findings are generally consistent with the LLRFbut not the differentiatorF model of vulnerability for AUDs (Quinn and Fromme, 2011;Morean and Corbin, 2010), suggesting that individuals with the BPP experienced a generalized decreased awareness of intoxication, which was not biphasic in character. Although the origins of this decreased awareness remain unclear, one possibility is that previous experiences of non-substancerelated mood elevation mean that individuals with BPP are less likely to attribute ethanol-induced mood variation (ie, intoxication) to alcohol.…”
Section: Discussionsupporting
confidence: 77%
“…However, given the conflicting findings of the literature, it is also possible that people with the BPP show greater stimulant effects during the ascending limb. We included only males in our experiment because problem drinking is more prevalent in men, and LLRs have been most robustly observed among men at-risk for AUDs (Quinn and Fromme, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…‘urge,’ ‘wanting’) contributed to the craving analysis ( k  = 16). For studies assessing craving at multiple points during the session, effects were averaged across time points at the study level (Quinn and Fromme, 2011). If studies reported data on more than one craving measure (e.g.…”
Section: Cravingmentioning
confidence: 99%
“…The inclusion of drinkers with such high intake and prior potentially rewarding experiences with heavy drinking may have enhanced their responses to liking alcohol and wanting more, especially if some met criteria for an AUD at baseline. Finally, the absence of differences for sedation or stimulation on the rising and falling limbs of the BrAC curves may not support the differentiator model as defined in some other articles (9,10).…”
mentioning
confidence: 99%